Hard X‐rays for processing hybrid organic–inorganic thick films. (1st January 2016) - Jiang, Yu; Carboni, Davide; Pinna, Alessandra; Marmiroli, Benedetta; Malfatti, Luca; Innocenzi, Plinio
Abstract : Hard X‐rays, deriving from a synchrotron light source, have been used as an effective tool for processing hybrid organic–inorganic films and thick coatings up to several micrometres. These coatings could be directly modified, in terms of composition and properties, by controlled exposure to X‐rays. The physico‐chemical properties of the coatings, such as hardness, refractive index and fluorescence, can be properly tuned using the interaction of hard X‐rays with the sol–gel hybrid films. The changes in the microstructure have been correlated especially with the modification of the optical and the mechanical properties. A relationship between the degradation rate of the organic groups and the rise of fluorescence from the hybrid material has been observed; nanoindentation analysis of the coatings as a function of the X‐ray doses has shown a not linear dependence between thickness and film hardness.